A refined self-tuning filter-based instantaneous power theory algorithm for indirect current controlled three-level inverter-based shunt active power filter under non-sinusoidal source voltage conditions - Yap, Hoon; Mohd Radzi, Mohd Amran; Hassan, Mohd Khair; Mailah, Nashiren Farzilah (MDPI, 2017)
In this paper, a refined reference current generation algorithm based on instantaneous power (pq) theory is proposed, for operation of an indirect current controlled (ICC) three-level neutral-point diode clamped (NPC) inverter-based shunt active power filter (SAPF) under non-sinusoidal source voltage conditions. SAPF is recognized as one of the most effective solutions to current harmonics due to its flexibility in dealing with various power system conditions. As for its controller, pq theory has widely been applied to generate the desired reference current due to its simple implementation features. However, the conventional dependency on self-tuning filter (STF) in generating reference current has significantly limited mitigation performance of SAPF. Besides, the conventional STF-based pq theory algorithm is still considered to possess needless features which increase computational complexity. Furthermore, the conventional algorithm is mostly designed to suit operation of direct current controlled (DCC) SAPF which is incapable of handling switching ripples problems, thereby leading to inefficient mitigation performance. Therefore, three main improvements are performed which include replacement of STF with mathematical-based fundamental real power identifier, removal of redundant features, and generation of sinusoidal reference current. To validate effectiveness and feasibility of the proposed algorithm, simulation work in MATLAB-Simulink and laboratory test utilizing a TMS320F28335 digital signal processor (DSP) are performed. Both simulation and experimental findings demonstrate superiority of the proposed algorithm over the conventional algorithm.